DEVELOPING CofiD-20 GAME FOR TEACHING READING COMPREHENSION TO THE TENTH GRADE STUDENT: RESEARCH AND DEVELOPMENT - Yudhi Irawan; Supriyono; Adin Fauzi (JOSAR (Journal of Students Academic Research), 2022)
The purpose of this study was to determine the game as a medium for learning reading comprehension that focuses on descriptive text, to determine English reading skills for learning reading comprehension, and to determine the ability of teachers and students' responses to the use of these media for learning reading comprehension in high school. The researcher adapted Sugiyono's research and development framework as a research reference. Adaptation is formulated in three phases, namely: basic research; design and development; and perception and finalization tests. The results showed that the game-based learning media had been validated by media and material experts and the responses of teachers and students had been carried out. The results of media experts 88.5% are included in the "Very Valid" category and an average of 81.3% material experts are included in the "Very Valid" category. The average teacher response was 87.2% included in the "Very Good" category and the average student response was 87.75% included in the "Very Good" category. From the results of the research above, it can be concluded that CofiD-20 Game as a learning media is valid and feasible to be used as a learning medium for learning reading comprehension.